Overconfidence and gender differences in wage expectations - Stephanie Briel; Aderonke Osikominu; Gregor Pfeifer; Mirjam Reutter; Sascha Satlukal (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2020)
We analyze the impact of (over-)confidence on gender differences in expected starting salaries using elicited beliefs of prospective university students in Germany. According to our results, female students have lower wage expectations and are less overconfident than their male counterparts. Oaxaca-Blinder decompositions of the mean show that 7.7% of the gender gap in wage expectations is attributable to a higher overconfidence of males. Decompositions of the unconditional quantiles of expected salaries suggest that the contribution of gender differences in confidence to the gender gap is particularly strong at the bottom and top of the wage expectation distribution.
urn:nbn:de:bsz:100-opus-18100
Keywords: J16; D84; D91; C21; 330; Gender Pay Gap; Wage Expectations; Overconfidence; Decomposition Analyses; Unconditional Quantile Regressions (RIF-Regressions)